1998
DOI: 10.1098/rspb.1998.0344
|View full text |Cite
|
Sign up to set email alerts
|

The spatial region of integration for visual symmetry detection

Abstract: Symmetry is a complex image property that is exploited by a sufficiently wide range of species to indicate that it is detected using simple visual mechanisms. These mechanisms rely on measurements made close to the axis of symmetry. We investigated the size and shape of this integration region (IR) by measuring human detection of spatially band-pass symmetrical patches embedded in noise. Resistance to disruption of symmetry (in the form of random phase noise) improves with increasing patch size, and then asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 22 publications
7
62
0
2
Order By: Relevance
“…These results implicate higher-level mechanisms in the detection of facial symmetry and rule out purely low-level mechanisms (although these could contribute as well). The sensitivity of facial symmetry detection to spatial scale corroborates this conclusion, because low-level symmetry detection mechanisms are insensitive to changes in spatial scale (Dakin & Hess 1997;Dakin & Herbert 1998;Rainville & Kingdom 2002).…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…These results implicate higher-level mechanisms in the detection of facial symmetry and rule out purely low-level mechanisms (although these could contribute as well). The sensitivity of facial symmetry detection to spatial scale corroborates this conclusion, because low-level symmetry detection mechanisms are insensitive to changes in spatial scale (Dakin & Hess 1997;Dakin & Herbert 1998;Rainville & Kingdom 2002).…”
Section: Methodssupporting
confidence: 67%
“…In addition to normal faces, we showed low, medium and high bandpass filtered faces, made using three separate bandpass filters of 1.4 octave width at half-height, with peak frequencies at 1.4, 10 and 60 cycles per face. Sensitivity to spatial scale would rule out purely low-level mechanisms, which are insensitive to spatial scale (Dakin & Hess 1997;Dakin & Herbert 1998;Rainville & Kingdom 2002). (ii) Stimuli Low, medium and high bandpass filtered versions were made for each of the faces used in experiment 1 (figure 3a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that symmetry detection may be a special case of orientation processing [6,7] in that once the axis of symmetry is determined, both this information and orientation information acquired from other contour classes converge at a common neural site where orientation information is processed irrespective of source. Further, Dakin and others have suggested that symmetry detection shares features with mechanisms responsible for processing orientation [8][9][10]. Symmetry is also thought to be important from an evolutionary perspective.…”
Section: Introductionmentioning
confidence: 99%